2011
DOI: 10.1371/journal.pone.0017067
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Screening for Spinal Muscular Atrophy (SMA) in 107,611 Pregnant Women during the Period 2005–2009: A Prospective Population-Based Cohort Study

Abstract: BackgroundSpinal muscular atrophy (SMA) is the most common neuromuscular autosomal recessive disorder. The American College of Medical Genetics has recently recommended routine carrier screening for SMA because of the high carrier frequency (1 in 25–50) as well as the severity of that genetic disease. Large studies are needed to determine the feasibility, benefits, and costs of such a program.Methods and FindingsThis is a prospective population-based cohort study of 107,611 pregnant women from 25 counties in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 42 publications
4
64
0
2
Order By: Relevance
“…Most often, SMA refers to the most common disease in this groupproximal SMA -which is further subdivided into four types based on clinical severity, as described in detail below (Engel, 2004;Wee, 2010). The incidence of SMA is between 1 in 6000 and 1 in 10,000 births (Su, 2011;Lorson, 2010;Pearn, 1978), making it the most common fatal autosomal recessive disorder (Prior, 2010).…”
Section: Spinal Muscular Atrophymentioning
confidence: 99%
“…Most often, SMA refers to the most common disease in this groupproximal SMA -which is further subdivided into four types based on clinical severity, as described in detail below (Engel, 2004;Wee, 2010). The incidence of SMA is between 1 in 6000 and 1 in 10,000 births (Su, 2011;Lorson, 2010;Pearn, 1978), making it the most common fatal autosomal recessive disorder (Prior, 2010).…”
Section: Spinal Muscular Atrophymentioning
confidence: 99%
“…Several pilot studies have been performed: in Israel with 168 pregnant and nonpregnant women (Basel-Vanagaite et al 2008); in Taiwan with 107,611 pregnant women from 383 primary clinics (Su et al 2011); and with 500 pregnant and non-pregnant women in the USA ). In the first two studies, no uptake rate was reported, whereas in the latter 60% accepted testing.…”
Section: Carrier Screening For Other Conditionsmentioning
confidence: 99%
“…SMA is an autosomal recessive disease and is a leading genetic cause of infant death worldwide with an incidence of 1 in 6000–10,000 births (Pearn, 1978; Cuscó et al., 2002). The carrier frequency for SMA is 1:25–50 in most populations (Ben-Shachar et al., 2011; Su et al., 2011; Sugarman et al., 2012; Lyahyai et al., 2012) though it is lower for some ethnicities (Zaldívar et al., 2005; Labrum et al., 2007; Hendrickson et al., 2009; Sangaré et al., 2014). SMA results from the loss or mutation of SMN1 ( survival motor neuron 1 ; OMIM #600354) on chromosome 5q13 (Lefebvre et al., 1995).…”
Section: Introductionmentioning
confidence: 99%